2013
DOI: 10.1111/pala.12024
|View full text |Cite
|
Sign up to set email alerts
|

Morphological disparity and developmental patterning: contribution of phacopid trilobites

Abstract: In trilobites as in many others extinct organisms, our understanding of the mechanisms of evolution is based on morphological and ontogenetic features. Data from ontogenetic development are essential to provide an insight into the origins of evolutionary changes. In phacopid trilobites, detailed studies of ontogenetic series have been achieved using quantitative methods. A comparison of ontogenetic trajectories of closely related species has been conducted to understand how the both morphological disparity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 62 publications
4
36
0
Order By: Relevance
“…An r 2 test shows that these are significantly correlated (0.68, p=0.0076), as do non-parametric tests for correlation (Spearman's rank: 0.77, p=0.0013; Kendall's tau: 0.58, p=0.0042). The raw total group diversity curve suggests trilobite diversity declined overall from the end-Cambrian, with these data not showing an early Ordovician radiation (unlike that observed for other groups during the Great Ordovician Biodiversification Event; see Servais et al, 2010), although there were clear diversity peaks in the Late Ordovician and Early Devonian (potentially reflecting the origination, and then diversification, of Phacopida; Crônier, 2013; and Proetida during the latter Epoch; Stubblefield, 1959). Figure 15 also supports the notion of trilobites having dramatically radiated early in the Cambrian (Webster, 2007).…”
Section: Interspecific Moulting Variability Through Timementioning
confidence: 81%
See 3 more Smart Citations
“…An r 2 test shows that these are significantly correlated (0.68, p=0.0076), as do non-parametric tests for correlation (Spearman's rank: 0.77, p=0.0013; Kendall's tau: 0.58, p=0.0042). The raw total group diversity curve suggests trilobite diversity declined overall from the end-Cambrian, with these data not showing an early Ordovician radiation (unlike that observed for other groups during the Great Ordovician Biodiversification Event; see Servais et al, 2010), although there were clear diversity peaks in the Late Ordovician and Early Devonian (potentially reflecting the origination, and then diversification, of Phacopida; Crônier, 2013; and Proetida during the latter Epoch; Stubblefield, 1959). Figure 15 also supports the notion of trilobites having dramatically radiated early in the Cambrian (Webster, 2007).…”
Section: Interspecific Moulting Variability Through Timementioning
confidence: 81%
“…This would extend along the entire anterior margin on the cephalon, and the animal would then emerge forwards. Other trilobites also evolved similar cephalic structures, such as later brachymetopid species with a greatly expanded rostral plate and fused facial sutures (Fortey and Owens, 1975), and many olenid and phacopid species which secondarily lost the facial sutures and moulted through disarticulation of the entire cephalon (discussed in detail later; Crônier, 2013;Drage et al, 2018b). Modern xiphosurans moult in a comparable manner to harpetids and trinucleids, also having a fused cephalic shield (carapace) in which a marginal gape opens between the dorsal and ventral parts (Sekiguchi et al, 1988).…”
Section: Moulting In Highly Derived Trilobitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies on trilobites have shown that the protaspid larval phase does not encompass the same developmental stages in all trilobites [92], casting doubt on the validity of the standard direct comparison between final stage protaspides. In order to account for these issues, it has been suggested that comparisons be made only when the entire ontogenetic series is taken into account [92], and recent work has attempted to characterise this both descriptively [93] and quantitatively [94] in a number of trilobite species. In many cases however the entire ontogenetic series will not be available for study, and although instars can be recognised as in the current study it is impossible to correlate these stages with certainty between species.…”
Section: Discussionmentioning
confidence: 99%